U-Pb detrital zircon geochronology and provenance of Neoproterozoic sedimentary rocks in southern Siberia: New insights into breakup of Rodinia and opening of Paleo-Asian Ocean - Gladkochub, D.; Donskaya, T.; Stanevich, A.; Pisarevskiy, Sergei; Zhang, S.; Motova, Z.; Mazukabzov, A.; Li, H. (Elsevier BV, 2019)
© 2018 International Association for Gondwana Research We present the synthesis of new data on detrital zircon geochronology of the Neoproterozoic strata of the southern part of the Siberian craton as well as a comprehensive analysis of previously published stratigraphic, sedimentological and geochronological (LA-ICP-MS) data obtained for key sections in this area that allows us to trace the process of birth and early stages of development of the Paleo-Asian Ocean (PAO). Before the break-up of Rodinia and opening of PAO, Tonian – Cryogenian intracontinental sedimentary basin existed between southern Siberia and northern Laurentia. The detachment of the southern flank of the Siberian craton from northern Laurentia and opening of the PAO between these cratons took place in Cryogenian. The detrital zircon ages from lower parts of Neoproterozoic successions suggest the Siberian craton as the sole provenance area right after the opening of the PAO. The age constraints on the lower parts of the studied Neoproterozoic successions, which are based on correlation of their tillite horizons with the Marinoan glaciation, suggest the late Cryogenian age for these sedimentary rocks. A clear change in the age spectra of detrital zircons from “unimodal” (Early Precambrian only) in older sedimentary rocks to “bimodal” (Early Precambrian as well as Neoproterozoic) in younger sequences of the studied successions marks the next stage of the PAO evolution. The abundance of youngest (630–610 Ma) detrital zircons in the upper parts of the studied sequences reflects a shrinkage of the oceanic basin as a result of the convergence of the craton with the microcontinents and island arcs within the Paleo-Asian Ocean. We suggest that a passive oceanic margin along the southern margin of the Siberian craton has been transformed into a series of foreland basins at ~610 Ma.